An Investigation on Multiple Intelligence of Students from the Faculty of Business Management (FPP) and Faculty of Computer and Mathematical Sciences ( FSKM), Universiti Teknologi MARA (UiTM) / Faiz Zulkifli ... [et al.] - Zulkifli, Faiz; Fadhullah, Afifah; Abu Bakar, Norida; Zainal Abidin, Rozaimah (UiTM Cawangan Johor, 2018)
The purpose of this study is to identify the multiple intelligence of students at Universiti Teknologi MARA (UiTM), Perak and Melaka Campuses. Two faculties are involved in this study which are Business Management (FPP) and Computer & Mathematical Sciences (FSKM). 81 FPP students and 43 FSKM students were respondents of this study which employed the multiple intelligences test identified by Howard Gardner. The survey consisted of nine intelligence areas which are linguistic, musical, logical-mathematical, spatial, bodily-kinesthetic, interpersonal, intrapersonal, naturalistic and existential. The surveys were conducted online throughout the semester. Descriptive analysis via frequency was performed using horizontal bar-chart to describe the data collected. Statistical Package for Social Sciences (SPSS) was used in the data analysis process to test the differences on multiple intelligences between the two faculties. Overall, FPP scores were higher than FSKM in all multiple intelligences. This research is supported by previous research done by Salehi and Germai (2012). Traditionally, Social Science students would typically be perceived to have more Linguistics Intelligence while Science Technology students would be perceived to have more Mathematical Intelligence. The findings can be used by educators to translate it into approaches in learning strategies and to incorporate it into the curriculum.